Influence of temperature on the dielectric and ferroelectric properties of bismuth titanate thin films obtained by the polymeric precursor method - Simoes, A. Z.; Ramirez, M. A.; Riccardi, C. S.; Ries, A.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2005)
The (1 1 7) and (0 0 1 0)-oriented Bi4Ti3O12 thin films were fabricated on Pt/Ti/SiO2/Si substrates by using a polymeric precursor solution under appropriate crystallization conditions. Atomic force microscopy and scanning electron microscopy showed relatively large grains, which is typical for this system. The capacitance dependence on voltage is strongly non-linear, confirming the ferroelectric properties of the films resulting from the domain switching. The (1 1 7)-oriented films exhibited a higher remanent polarization (23.7 μ C cm(-2)) than the (0 0 1 0)-oriented films (11.8 μ C cm(-2)). Fatigue tests revealed that the temperature of thermal treatment and degree of orientation affect the performance of the device. © 2005 Elsevier B.V. All rights reserved.
Keywords: bismuth titanate; thin film; dielectric properties; ferroelectric properties